Effect of Fungal Inoculation to Resin Content on Gaharu Plants (Gyrinops Versteegii (Gilg.) Domke) - I Made Mega; I Wayan Nuarsa (International Journal of Environment and Geosciences, 2019)
One of the commodities of non-timber forest products (NTFPs) is agarwood sapwood which has high economic value as an export commodity, as well as a good source of income for the community. Agarwood sapwood is an aromatic substance in the form of a lump that is found between wood cells in a variety of distinctive shapes and colors and has a resin content (mastic). Resin is a secondary metabolite compound produced by agarwood plants due to injury or infection by microbes. One of the microbes that infects the agarwood plant is a variety of fungi. This study aims to obtain a type of fungi that is effective in the formation of resin compounds in agarwood plants. This research is a field experiment with randomized block design. The treatments that experimented were mushroom inoculation, namely: J0 (without fungal inoculation), JF (Fusarium solani mushroom inoculation), JR (inoculation of Rhisopus sp), JT (inoculation of Trichoderma sp). Each treatment was repeated 4 times. Parameters observed were: sap color, sap smell, infection width and length, and resin content in sapwood (%). Data were analyzed statistically by variance test (ANOVA). If the treatment has a significant effect, followed by a BNT test at the level of 5%. The results showed that the treatment of fungi inoculation significantly affected the width of the infection and the sap content of sapwood, while the other parameters had no significant effect. The best treatment was obtained in JT (inoculation of mushroom Trichoderma sp.) with the results in the form of sap with: the color of the sap ranged from brown to blackish brown; fragrant aroma, infection length (2.39 cm) and infection width (1.11 cm), and resin content of 7.92%.